The mediating role of technology anxiety in the impact of loneliness on technology behavioral intention among community-dwelling older adults - Chih-Yu Tsai; Ya-Ling Tzeng; Yu-Kuei Teng; Ting-Shan Chang (PLoS ONE, 2025)
In this modern digital era, older adults encounter considerable challenges in technology adoption, primarily due to varying degrees of technology anxiety and its implications on their behavioral intentions. We conducted a cross-sectional survey with 250 participants aged 60 and older in Taiwan to investigate the mediating role of technology anxiety in the dynamic between loneliness and technology usage intentions. The results reveal that participants exhibited mild levels of loneliness (mean score: 1.53), moderate technology anxiety (mean score: 19.29), and moderate to high intentions toward technology use (mean score: 10.96). The study identifies a significant total effect of loneliness on technology behavioral intention (c = -0.508, p < 0.001). Specifically, loneliness was found to significantly influence technology anxiety (a = 1.158, p < 0.001), which in turn significantly impacted behavioral intention, even after adjusting for loneliness (b = -0.161, p < 0.001). Technology anxiety partially mediated the relationship between loneliness and behavioral intention, exacerbating its negative impact (c’ = -0.322, p < 0.001). These findings highlight the critical need for targeted interventions and policy measures to address and mitigate the barriers to technology adoption faced by older adults.